Melatonin and sleep parameters in infertile women with endometriosis: first results from the triple-blind randomized controlled trial of administration of melatonin in chronic pelvic pain and sleep disturbance - Sedighe Esmaeilzadeh; Fatemeh Habibolahi; David Moher; Zahra Basirat; Hemat Gholinia; Masoumeh Golsorkhtabaramiri; Parvaneh Mirabi (PLoS ONE, 2025)
Introduction To evaluate the effect of melatonin supplementation on sleep quality and pelvic pain in infertile women with endometriosis and sleep disturbances. Materials and analysis A randomized, triple-blind, placebo-controlled trial was conducted among 80 infertile women with endometriosis and sleep disturbances. Participants were randomly assigned to receive either 5 mg melatonin or placebo for 2 months. The primary outcome was change in overall sleep quality as measured by the Pittsburgh Sleep Quality Index (PSQI). Secondary outcomes included changes in specific PSQI domains and chronic pelvic pain. Result Among 80 infertile women with endometriosis and sleep disturbances, melatonin significantly improved overall sleep quality compared to placebo, with a large effect size (p < 0.001, η² = 0.20, Cohen’s d=1). The mean difference in sleep quality was a reduction of -1.7 on the PSQI, although it did not reach the clinically meaningful threshold of 3 points. Melatonin also led to considerable improvements in specific PSQI domains including: a substantial increase in sleep duration and a marked reduction in sleep disturbances. Furthermore, melatonin significantly decreased sleep latency, exhibiting a large effect size, and contributed to a medium reduction in the use of sleep medications. However, no significant improvements were noted in sleep efficiency, daytime dysfunction, or subjective sleep quality. Additionally, melatonin significantly reduced chronic pelvic pain, with a large effect size (p < 0.001, η² = 0.18, Cohen’s d = 0.93). Conclusion While melatonin may improve sleep quality and reduce pelvic pain, further investigation is needed to assess its clinical relevance in this population. Trial registration ClinicalTrials.gov IRCT20171209037794N4.